Réponses

Meilleure réponse !
2014-03-19T13:48:33+01:00

A= 3*(x+5)

A = 3x + 15
B= 3x*(-4+x)

B = - 12x + 3x²
C= 3(b-4)

C = 3 b - 12
d= -w(-1+w)

d= w - w²
e= -4(7+u)

e= -28 - 4u
f= -2y(3y+5)

f = -6 y² -10 y
g= -2(5x-1)

g = -10x +2
h= -3a(6-5a)

h = -18a + 15 a²
I= (x+1)(x+5)

I= x² + 5x + x +5 = x² + 6x + 5
J=(4x+5)(2x+6)

J = 8x² + 24x + 10 x + 30 = 8 x² +34x +30
k=(5u+1)(2-3u)

k = 10 u - 15 u² +2 - 3u = - 15u² + 7 u +2
L=(-3+n)(-2n-5)

L = 6 n +15 - 2 n² - 5 n = -2n² + n + 15


c'est tres gentil de votre part
je t' en prie!
pouvez vous m aider pour un devoir que j ai poste
voici le lien http://nosdevoirs.fr/devoir/256421
Merci à toi!